Review on the Actively-Controlled Colloidal Dampers and Investigations on a Colloidal Damper Rendered Controllable under the Variable Magnetic Field Generated by Moving Permanent Magnets - Barenten Suciu (Newest Updates in Physical Science Research Vol. 7, 2021)
In this Chapter, following a discussion on the working principle of a colloidal damper rendered controllable (CDRC), a review of various types of controlling devices and their sensitivity, is presented. Then, a new type of colloidal absorber, rendered controllable under the variable magnetic fields, is proposed and its controllability is experimentally evaluated. This absorber employs a water-based ferrofluid (FERROTEC MSG-W10) in association with a liquid-repellent nanoporous solid body, consisted of particles of gamma alumina and/or silica gel. Control of the dynamic characteristics is obtained by moving permanent neodymium annular magnets, which are placed either on the piston head (axial magnetic field) or on the external surface of the cylinder (radial magnetic field). In order to properly select these magnets, flow visualizations inside of a transparent model damper were performed, and the quantity of the displaced liquid by the magnets through the damper’s filter and through the nanoporous solid body was determined. Experimental data concerning the variation of the magnetic flux density at the magnet surface versus the height of the magnet, and versus the target distance was collected. Based on such data, the suitable magnet geometry was decided. Then, the three-dimensional structural model of the trial colloidal damper obtained by using Solidworks, and the excitation test rig are presented. From excitation tests on a ball-screw shaker, one confirmed larger damping abilities of the proposed absorber relative to the traditional colloidal damper, and also the possibility to adjust the damping coefficient according to the excitation type.